An exploration of adolescents' perceptions of X-ray examinations. Issue 2 (May 2015) - O' Shea, C.; Davis, M.
Abstract Purpose The research presented in this paper is taken from a larger study whose aims were to explore adolescents' perceptions of X-ray examinations and more specifically middle adolescents' perceptions of X-ray examinations. Middle adolescents are between the ages of 15 and 17 years and experience many changes in their lives that differentiate them from young and late adolescents. There is limited research available on middle adolescents' perceptions of the X-ray examination process Methodology 18 adolescents, age range 15–17 years, took part in the research study. This included 9 male and 9 female adolescents from 2 secondary schools in the Dublin area. A self-completion questionnaire was used as the method of investigating their perceptions of the X-ray examination process. The data, which consisted of feelings and opinions, was analysed qualitatively using thematic analysis. Results Analysis suggested that the adolescents perceived that the 'wait' in the waiting room was long and boring. They expressed an interest in the provision of suitable recreational facilities to distract them from feeling nervous, bored and from the pain they felt. 16 of the adolescents found the X-ray examination interesting, although they appeared to have little knowledge of what was happening. 14 of the adolescents perceived the radiographer to be friendly. More boys than girls complained about the radiographer. Conclusion The study indicates that middle adolescents are not receiving effective quality care that meets their specific needs when presenting for an X-ray examination. Further research could help in providing the adolescents with the optimum care they need.